2011
DOI: 10.2337/dc10-2341
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Impact of Diabetes on Mortality in Patients After Major Lower Extremity Amputation

Abstract: OBJECTIVETo estimate the impact of diabetes on mortality in patients after first major lower extremity amputation (LEA).RESEARCH DESIGN AND METHODSUsing claims data of a nationwide statutory health insurance, we assessed all deaths in a cohort of all 444 patients with a first major LEA since 2005 (71.8% male; mean age 69.1 years; 58.3% diabetic; 43% with amputation above the knee) up to 2009. Using Cox regression, we estimated the time-dependent hazard ratios to compare patients with and without diabetes.RESUL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
70
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 19 publications
12
70
0
4
Order By: Relevance
“…Our IHM of 10.0% is consistent with previously reported data ranging from 7% to 12.4% [7, 10, 3033]. Investigation of underlying influences from health services, surgical decisions and patient motivations behind decisions to amputate might help to explain some of the differences in post-operative mortality rates between studies [34].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our IHM of 10.0% is consistent with previously reported data ranging from 7% to 12.4% [7, 10, 3033]. Investigation of underlying influences from health services, surgical decisions and patient motivations behind decisions to amputate might help to explain some of the differences in post-operative mortality rates between studies [34].…”
Section: Discussionsupporting
confidence: 90%
“…The effect of advancing age on IHM is also highlighted in this study, as has been well established by other authors [7, 10, 30]. Older age is associated with high prevalence of comorbid conditions, mainly cardiovascular and renal diseases, both of which are also associated with higher mortality rates [32, 35].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A major amputation was associated with an adverse outcome and reduced long-term survival. 18,19 These results are further supported by the studies of Larsson et al 12 and Faglia et al 20 We observed a highly significant difference in the comparison of long-term survival between groups II and III. The median survival rate in group III was 15 months longer than in group II.…”
Section: Discussionsupporting
confidence: 82%
“…Diabetic foot disease is associated with impaired quality of life [4,5] and high mortality. After primary ulceration, 5-year mortality rates have been estimated to be 42-44% and after amputation they are estimated to be 68-79% [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%